Análise de propostas de regulamentações para Inteligência Artificial e suas aplicações - Sousa, Nájala Kelly Lima de (2025)
This work aims to address the various areas of artificial intelligence applications and their impact on society, present a case study involving 14 countries that shows the approaches each government is taking to handle and develop applications using artificial intelligence. These approaches were divided into two groups: countries that chose to create specific legislation for the use of artificial intelligence, and countries that adopted a more lenient strategy regarding its use. Lastly, the creation of an application using the Python programming language and the concepts of natural language processing (NLP) is presented. This application extracts tokens from texts, processes these tokens, and ultimately counts the most frequently mentioned words in the studied documents. Through this process, it is possible to gain a broader understanding of the main concerns and interests of governments regarding the use of AI. Finally, by exploring the models chosen by the countries and the consequences of artificial intelligence applications, the laws addressed in the strategies of countries that opted for the development of AI solutions do not guarantee the rights, security, and privacy of citizens.